On the Buoyancy Subrange in Stratified Turbulence - Victor Avsarkisov (Atmosphere, 2020)
This study is motivated by the importance of the stratified turbulence in geophysical flows. We present a theoretical analysis of the buoyancy subrange based on the theory of strongly stratified turbulence. Some important turbulent scales and their relations are explored. Scaling constants of the buoyancy subrange scaling laws for both kinetic and potential energy spectra are derived and analyzed. It is found that these constants are functions of the horizontal Froude number <semantics> F r h </semantics> . For the potential energy spectrum, the scaling constant also depends on the turbulent flux coefficient of <semantics> Γ </semantics> .